PRODUCTIVITY OF WINTER WHEAT VARIETIES DEPENDING ON TERMS OF SOWING IN THE CONDITIONS OF NORTHERN PART OF THE LEFT BANK STEPPE OF UKRAINE - Мельник, А. В.; Собко, М. Г.; Дубовик, О. О. (Scientific Progress & Innovations, 2013)
Thus, the optimal conditions for the northern part of the Left Bank steppe of Ukraine sowing dates should be considered 10-th – 20-th of September. For most varieties sowing on September the 20-th contributed to greater performance of their genetic potential in terms of productivity. The stated regularity of productivity loss have been stated at a deviation from the optimum sowing time to earlier (September the 10-th) and later (1-st and 10-th of October). Sowing in the later periods in most years leads to greater yield reduction than at early sowing.